Influence of Strength-Building Activities on Competitive Results of Athletes in Workout - Iryna Malyarenko; Yuriy Romaskevych; Olha Koltsova; Kateryna Yuskiv (Lesya Ukrainka Volyn National University, 2018)
Relevance of the investigation is caused by regularities of the origin and development of Workout as one of the directions of strength gymnastics, to achieve results in which the level of the development of strength qualities plays an important role. Analysis of the up-to-date studies on Workout development points out the need to draw attention to peculiarities in the organization and methods of providing training sessions. The necessary physical preparation and high sports results can be achieved by taking in consideration all factors and the rational structure of training process. The purpose of investigation - to work out a method of strength training in Workout and to check it up in competition activities. Results of investigation. A modern trend of strength-building acrobatics «Street workout» appeared as the variety of bodybuilding and is based on gymnastic exercises. Workout - English-American term is translated as «training» and composed of the complex of physical exercises directed to the improvement of strength, strength endurance and body shape. Therefore, exercises in speed-and-strength moves and methods of static and isometric exercises are used in special training. The trainings that are provided in different regimens and give significant results are considered as special methods of the development of strength, in which the variety of the regulations of tension in different regimens of their work, namely, isometric, concentric, eccentric, is of great importance. The article claims that the most effective ways and methods of strength development in Workout are varieties of exercises «Finger-tip push-up» (press-ups), method of isometric and static tensions, Tabat's protocol. The analysis of our  experimental findings has proven that the developed methods of strength training of athletes-workouters provide the most significant increase in the results of control exercises «Horizontal backward hang», «Muscle-up on horizontal bar», «Push-ups from the floor» and «Arm balance».  In the process of the investigation, a direct correlation between strength preparedness and the results of competitions in the exercise «Chest Dips with additional weight»; between strength preparedness and the final results of competitions in Workout was established. The obtained data are confirmed by the results of sportsmen's participation in regional competitions in Street Workout.